Superficial Branch of Radial Nerve in Fetuses - Harjeet Kaur1DaisySahni, Richa Gupta, Anjali Aggarwal, Tulika Gupta, (International Journal of Scientific Research and Management (IJSRM), 2017)
Despite a careful approach by majority of the surgeons, damage to these branches may occur inadvertently, leading to paraesthesia, hypesthesia, and painful neuromas. The aim of this study was to demonstrate anatomic variations of the superficial branch of the radial nerve (SBRN) and to discuss the importance of this branch for neonatal surgical approaches. 30 spontaneously aborted fetuses (21 males, 9 females; age between 24 and 36 weeks) were dissected. In 56.7% of the cases, SBRN emerged from beneath the brachioradialis muscle at level of lower one third of forearm, while in rest of the cases, it emerged at the level of lower one third of forearm. it was observed to be penetrating beneath he SBRN became subcutaneous at level of lower one third of forearm in 70% of the cases, while in rest of the cases, it was at level of lower one third. This distance was found to vary from6.33 to 11.45 mm.Branches of the SBRN which are close to the first dorsal compartment may be injured while releasing the compartment. For this reason, during this operation, attention should be paid to the existence of the SBRN branches, especially in the first dorsal compartment.s.